Pendampingan Pemberdayaan Desa Biting Melalui Prinsip Asset-Based Community Development (ABCD) dalam Program 'Nusa Loe' Menuju Desa Mandiri Manggarai Timur - Petrus Frensi Mase; Dandy Patria W.; Sapto Pramono (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study analyzes the implementation of Asset-Based Community Development (ABCD) principles in the 'Nusa Loe' program in Biting Village, East Manggarai. The ABCD approach emphasizes utilizing local assets such as social networks, cultural traditions, natural resources, and human skills as the foundation for sustainable development and community independence. The program begins with an asset mapping activity led by the community, enabling the identification of the village's strengths from five key aspects: human, social, natural, institutional, and cultural assets. Through active participation, the community designs and implements development activities based on local potentials, replacing the conventional development paradigm that focuses on deficiencies and needs. The qualitative research approach employs in-depth interviews, participatory observations, and data triangulation to understand the shifts in mindset and community empowerment. The findings show that the implementation of ABCD successfully transformed the community's mindset, previously dependent on external aid, into a more independent and self-confident one. For example, Mr. Petrus, who improved the economic value of local coffee products after attending a coffee roasting training, and Mrs. Maria, who emphasized the importance of social capital and solidarity in supporting the sustainability of village businesses. The strengthening of cultural assets and local traditions, such as the Caci dance and customary rituals, was also integrated into the village's development plans and institutional management. The 'Nusa Loe' program demonstrates that asset-based empowerment can build a self-reliant, innovative, and sustainable village in the face of development challenges.